Evolusi Pemasaran Digital: Dampak Teknologi dan Media Sosial terhadap Perilaku Konsumen dan Strategi Bisnis - Sari, Santi Romarantika; Ayunda, Kirana Sekar (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Digital marketing has become a vital element of modern business strategy, transforming how companies engage with consumers through technology, data analytics, and interactive platforms. This study aims to explore the evolution of digital marketing and examine how emerging technologies such as social media and artificial intelligence (AI) influence consumer behavior and the design of marketing strategies. Using a literature review approach, this paper analyzes recent studies related to digital marketing, social media, and AI applications in business contexts. The findings reveal that while digital technologies create vast opportunities for personalization, efficiency, and data-driven decision-making, companies in Indonesia continue to face challenges regarding technology adoption, data privacy, and ethical issues in AI usage. Therefore, businesses must develop adaptive and sustainable marketing strategies that balance technological innovation with social values and a deep understanding of consumer behavior. The study highlights that successful digital marketing in the future will depend not only on technological advancement but also on the ability of organizations to integrate ethical responsibility, transparency, and sustainability into their strategic frameworks. This paper contributes to the growing body of literature on digital marketing by emphasizing the importance of responsible technology utilization in developing more relevant, competitive, and enduring business strategies in the digital era.